TRANSFORMASI AKUNTANSI NIRLABA: PERSEPSI MAHASISWA AKUNTANSI TERHADAP TANTANGAN DAN PELUANG DI ERA DIGITAL STUDI MAHASISWA AKUNTANSI KEUANGAN PUBLIK POLITEKNIK BALEKAMBANG JEPARA - Wardani, Nila Ayu Kusuma (ITB AAS Indonesia Surakarta, 2025)
AbstractThis study aims to explore the perceptions of public financial accounting students of Balekambang Jepara Polytechnic towards the challenges and opportunities in the transformation of non-profit accounting in the digital era. In addition, this study also seeks to identify the gap between the skills possessed by students and the needs of the non-profit sector and provide strategic recommendations for the development of a curriculum that is more in line with the needs of the digital era. The research method used is a qualitative approach with a case study method. Data were collected through in-depth interviews with Public Financial Accounting students of Balekambang Jepara Polytechnic and analyzed using thematic analysis techniques to identify key themes related to students' perceptions and readiness for the digitalization of non-profit accounting. The results of the study indicate that although students are aware of the importance of digitalization and see opportunities in the use of technology to improve efficiency and transparency in the non-profit sector, they feel less prepared due to limited digital skills and minimal exposure to non-profit accounting practices. This study emphasizes the need for curriculum updates to include materials on digital technology and non-profit accounting, as well as the provision of relevant practical training. Thus, students will be better prepared to face the challenges and take advantage of the opportunities offered by the digital transformation in the non-profit sector.Keywords: Non-Profit Accounting, Digital Age, Accounting Students